Nilai Nilai Pancasila dalam Kehidupan Sehari-Hari - A. Ramli Rasyid; Asrianti Asrianti; Odilia Yusri Putri; Muh. Fadlan Fauzan; Muh. Feryansyah Sandy (Syntax Corporation Indonesia, 2024)
Currently, it is the duty of the people of our country to apply the values ​​of Pancasila in social life. Because, the values ​​of Pancasila are the foundation of the Indonesian nation and are the life guidelines of Indonesian society. Currently, knowledge, understanding and practice of Pancasila values ​​for the Indonesian generation of young men and women are increasingly being eroded by the influx of new values ​​that are at odds with the nation's own identity. This means that a person will face many problems, both from within and outside the scope, now and in the future. To overcome these problems, it is necessary to renew Pancasila values ​​so that they can become a reference in dealing with various problems faced by Indonesian society now and in the future. To achieve the ideals of the Proclamation, the basic values ​​of Pancasila must be known, understood and practiced in the daily life of society in Indonesia. The Pancasila values ​​contained in Pancasila as the basis of our nation state are belief in the Almighty God, democracy and the unity of Indonesia.